Effect of eccentric mass on rotor dynamics as a source of harvesting energy vibration - Muhammad Noor Al-Fauzan Syahputra; Subekti Subekti; Nur Indah (JTTM : Jurnal Terapan Teknik Mesin, 2024)
This research focuses on the potential for vibration energy from the use of eccentric masses in dynamic rotors to become an electrical energy source. Prior studies on eccentric mass in dynamic rotors were primarily concerned with examining the rotor's vibrational characteristics; however, little research was done on converting vibrational energy into electrical energy. The purpose of this study is to ascertain the maximum amount of electrical energy that can be produced by dynamic rotor vibrations using an eccentric mass. Utilizing an electromagnetic energy harvester, an experimental study is the methodology used. With a rotor rotation speed of 450 rpm, the eccentric mass variations used are 6.5 grams, 8.5 grams, and 10.5 grams. Matlab is used in this research to process data. The highest energy, using an eccentric mass of 8.5 grams, was found to be 24.15 mV. Nevertheless, this study shows that while the eccentric mass has an impact on the amplitude, it has no effect on the voltage. In order to increase and improve the efficiency of the electrical energy produced, further research on the utilization of vibration energy from dynamic rotors can be guided by the findings of this study